KREDIBILITAS KEPEMIMPINAN PENDIDIKAN - Mashuri (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2021)
The credibility of educational leadership is very important and even the life of a leader. Leaders who have credibility, then subordinates work sincerely, loyally and have a high sense of belonging to the organization. In addition, what is more important is the positive implication on the performance of educators and education personnel and on the quality of graduates. Conversely, if an educational leader has low credibility, then subordinates will work carelessly, work if they are rewarded and supervised and the sense of belonging to the organization is very low or even non-existent. And what's worse is the impact on the decline in the performance of subordinates and the low quality of graduates. This study uses a descriptive qualitative approach. The results showed that the credibility of educational leadership in general was good. Where educational leadership has implemented what is an indicator of credibility, which has implemented a good attitude of honesty, fairness, responsibility and the ability to inspire subordinates. However, there are still things that have not been implemented optimally, namely those related to interactional and distributive justice in terms of unequal reward and intensity that is still lacking and the ability to inspire in the motivating aspect has not used symbols in educational institutions.